2016
DOI: 10.12965/jer.1632650.325
|View full text |Cite
|
Sign up to set email alerts
|

The effects of strength exercise and walking on lumbar function, pain level, and body composition in chronic back pain patients

Abstract: The beneficial effects of a strength exercise program and a combined exercise program of strength training plus walking were examined in overweight with chronic back pain patients. The participants were randomly placed in the strength exercise group (SEG, n=15), combined exercise group (CEG, n=15), and control group (CG, n=6). All subjects performed exercise twice per week, 50 min per session with a professional instructors for 12 weeks. In order to evaluate exercise intervention effects, lumbar function was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
1
19
2
Order By: Relevance
“…Pollock and Gettman 9 ) reported that weight training was a significant method for people with low back pain. Similar to this finding, Lee 10 ) used a resistance exercise and lumbar stabilizing exercise in increase lumbar strength and to reduce pain. These two researchers found the effects of weight bearing exercise enhanced lower back muscle strength.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Pollock and Gettman 9 ) reported that weight training was a significant method for people with low back pain. Similar to this finding, Lee 10 ) used a resistance exercise and lumbar stabilizing exercise in increase lumbar strength and to reduce pain. These two researchers found the effects of weight bearing exercise enhanced lower back muscle strength.…”
Section: Discussionmentioning
confidence: 58%
“…Although, weight bearing exercise programs have many additional health benefits for low back patients, our study focused on 8-types of back stretching exercise. An increase in low back muscle flexibility would maximize the low back muscular strength, preventing low back pain and reducing the risk of injuries 10 ) . Therefore, muscular flexibility and balanced growth of muscular strength are the fundamental elements for of building a correct posture 9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with other studies indicating that strengthening exercises reduced pain and disability associated with LBP after 6 weeks to 12 months of the exercise program. [26][27][28][29][30][31] Likewise, core muscle strengthening for at least 3 months was beneficial in aspects of pain relief and functional improvement. Nevertheless, no significant difference was demonstrated in exercise groups up to 12 months compared with the exercise group of over 12 months for participants with chronic LBP.…”
Section: Discussionmentioning
confidence: 96%
“…Hashimoto et al found that objectively measured physical activity is negatively correlated to LBP [25]. Lee and Kang also stated that the combination of walking and strength exercise might improve LBP symptoms [26]. The effects of other forms of exercise, including walking, should be explored further in future studies.…”
Section: Discussionmentioning
confidence: 99%